Chemoprophylactic activity of flubendazole in cystic echinococcosis - Ceballos, Laura (2010)
Background: Cystic echinococcosis (CE) is an important public health problem worldwide. Flubendazole, administered in tablets, has shown poor in vivo efficacy against CE in humans. However, flubendazole prepared as a solution caused a marked reduction in hydatid cysts developed in mice. The goal of the current work was to compare the chemoprophylactic effect of flubendazole formulated either as a hydroxypropyl-β-cyclodextrin solution or as a carboxymethylcellulose suspension in secondary CE in mice. Methods: Balb/C mice were infected with Echinococcus granulosus protoscoleces. One day after infection, the animals were allocated into 3 different experimental groups: unmedicated control and treated at the time point of infection with flubendazole either prepared as a solution or suspension given twice a day during 15 days. Six months after infection, the animals were sacrificed to collect and weight parasitic cysts. Cyst samples recovered from infected mice of each experimental group were prepared for both scanning and transmission electron microscopy. Results: Both flubendazole formul tions induced a significant reduction in cyst weight compared to the cysts recovered from the unmedicated control animals. Both formulations showed similar flubendazole-induced ultrastructural morphological changes. Conclusion: Flubendazole offers a great potential to become a drug of choice in the preventive treatment of cystic echinococcosis.